Epidemiology of khat (Catha edulis) consumption among university students: a meta-analysis - Getinet Ayano; Kalkidan Yohannis; Mebratu Abraha (BMC, 2019)
Abstract Background Khat is amphetamine-like substance commonly consumed by students when they wish to study for long hours especially during examination periods. Khat consumption is associated with increased rates of cardiovascular problems, stroke, myocardial infarction, cardiomyopathy, periodontal disease, gastritis, poor oral hygiene, psychosis, decreased quality of life, and poor academic performance. Methods PubMed, EMBASE, and SCOPUS were systematically searched without restriction by publication status. Publications were screened according to predefined inclusion criteria. Twenty-five articles were included. Random effect model was used to calculate weighted prevalence, odds ratio (OR) and corresponding 95% confidence interval (CI). We assessed the risk of publication bias by using funnel plot and Eggers's regression tests. Results The pooled prevalence of current khat use among university students was 14.16% (95% CI; 11.87-16.81). The pooled prevalence of current khat use was highest in Saudi Arabia 18.85% and it was 13.59% in Ethiopia and 13.04% in Yemen. In addition, the current pooled prevalence of khat use was higher in men at 19.26% than in women 6.41%. Regarding lifetime khat use, in this study, the pooled prevalence of lifetime khat use was 27.31%. The lifetime prevalence was higher in men at 31.47% than in women 11.79%. Moreover, the lifetime prevalence of khat use was 43.27% in Yemen, 37.32% in Saudi Arabia, and 24.82% in Ethiopia. We found significantly increased odds of current (OR 3.59; 95%CI 2.01-6.41) as well as lifetime (OR 3.48; 95%CI 2.09-5.78) khat chewing in men as compared to women. Conclusion The pooled prevalence of current and lifetime khat consumption was 14.16 and 27.31%, respectively. Both the current and lifetime prevalence of khat use was higher in men than in women. In addition, both the current and lifetime prevalence estimates of khat consumption were low in Ethiopia than in Saudi Arabia. Moreover, the odds of both current and lifetime khat consumption were higher in male students than in female students. Programmes that specifically aim at increasing awareness and that most motivate reduced khat consumption among university students were recommended.